2006
DOI: 10.2174/187152706778559273
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Depression and Hippocampal Apoptosis

Abstract: In this review, we summarize and discuss recent studies on structural plasticity changes, particularly apoptosis, in the mammalian hippocampus in relation to stress and depression. Apoptosis continues to occur, yet with very low numbers, in the adult hippocampal dentate gyrus (DG) of various species. Stress and steroid exposure modulate the rate of apoptosis in the DG. Contrary to earlier studies, the impact of chronic stress on structural parameters of the hippocampus like cell number and volume, is rather mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
149
1
8

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(163 citation statements)
references
References 1 publication
5
149
1
8
Order By: Relevance
“…Particularly, within the hippocampus, there is a close association between apoptosis and neurogenesis and the precise balance drives the continuous turnover of cells in this region (Biebl et al, 2000;Heine et al, 2004). Besides slowing down neurogenesis, stress and steroid hormones temporally reduce the dentate cell turnover, by modulating the ongoing rate of apoptosis (Lucassen et al, 2006;Czeh and Lucassen, 2007). Although, the impact of chronic stress on total hippocampal cell number and volume is modest (o10%) and these changes are transient, the functional consequences on dentritic arborization and synaptic plasticity over time could contribute to the structural impairments observed in depressive disorders (Lucassen et al, 2006;Czeh and Lucassen, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Particularly, within the hippocampus, there is a close association between apoptosis and neurogenesis and the precise balance drives the continuous turnover of cells in this region (Biebl et al, 2000;Heine et al, 2004). Besides slowing down neurogenesis, stress and steroid hormones temporally reduce the dentate cell turnover, by modulating the ongoing rate of apoptosis (Lucassen et al, 2006;Czeh and Lucassen, 2007). Although, the impact of chronic stress on total hippocampal cell number and volume is modest (o10%) and these changes are transient, the functional consequences on dentritic arborization and synaptic plasticity over time could contribute to the structural impairments observed in depressive disorders (Lucassen et al, 2006;Czeh and Lucassen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, antidepressants are hypothesized to mediate their long-term therapeutic effects by triggering cellular protective mechanisms to counteract the structural impairments Duman, 2004;Lucassen et al, 2006). In support of this hypothesis, chronic ADT increases the expression of brain-derived neurotrophic factor (BDNF; Nibuya et al, 1995) and neurogenesis in the adult hippocampus (Malberg et al, 2000) as well as enhances cell proliferation in the Fr cortex (Kodama et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathological studies showed that neurodegenerative diseases affect hippocampal subfields differently, e.g. neuronal loss was found especially in the CA1 area in Alzheimer disease [11][12][13]. Recently attention has been given also to brain metabolites and changes of their content during aging.…”
Section: Introductionmentioning
confidence: 99%